Internet of Things (IoT) and its role in telecommunications (Eurasian Scientific Herald, 2024)
Modern challenges and prospects of the Internet of Things (IoT) is a technological paradigm that units many devices for data exchange and automation in various fields. This article explores the relationship between IoT and telecommunications, discussing their interaction, technological aspects and applications in various fields. The principles and features of IoT, the impact of telecommunications on its development and communication technologies used to ensure the functioning of IoT networks are analyzed. The article examines the application of IoT in healthcare, smart cities, industry and the automotive sector, taking into account the role of telecommunications in these areas. The authors emphasize the challenges and prospects of IoT development, as well as the need for further research and improvement of telecommunications infrastructure for effective IoT operation